Transient Nutrient Deprivation Promotes Macropinocytosis-Dependent Intracellular Bacterial Community Development - Rachael L. Hardison (American Society for Microbiology, 2018)
ABSTRACT Nutrient limitation restricts bacterial growth in privileged sites such as the middle ear. Transient heme-iron restriction of nontypeable Haemophilus influenzae (NTHI), the major causative agent of chronic and recurrent otitis media (OM), promotes new and diverse phenotypes that can influence planktonic, biofilm, and intracellular lifestyles of NTHI. However, the bacterial responses to nutrient restriction that impact intracellular fate and survival of NTHI are unknown. In this work, we provide evidence for the role of transient heme-iron restriction in promoting the formation of intracellular bacterial communities (IBCs) of NTHI both in vitro and in vivo in a preclinical model of OM. We show that transient heme-iron restriction of NTHI results in significantly increased invasion and intracellular populations that escape or evade the endolysosomal pathway for increased intracellular survival. In contrast, NTHI continuously exposed to heme-iron traffics through the endolysosomal pathway for degradation. The use of pharmacological inhibitors revealed that prior heme-iron status does not appear to influence NTHI internalization through endocytic pathways. However, inhibition of macropinocytosis altered the intracellular fate of transiently restricted NTHI for degradation in the endolysosomal pathway. Furthermore, prevention of macropinocytosis significantly reduced the number of IBCs in cultured middle ear epithelial cells, providing evidence for the feasibility of this approach to reduce OM persistence. These results reveal that microenvironmental cues can influence the intracellular fate of NTHI, leading to new mechanisms for survival during disease progression. IMPORTANCE Otitis media is the most common bacterial infection in childhood. Current therapies are limited in the prevention of chronic or recurrent otitis media which leads to increased antibiotic exposure and represents a significant socioeconomic burden. In this study, we delineate the effect of nutritional limitation on the intracellular trafficking pathways used by nontypeable Haemophilus influenzae (NTHI). Moreover, transient limitation of heme-iron led to the development of intracellular bacterial communities that are known to contribute to persistence and recurrence in other diseases. New approaches for therapeutic interventions that reduce the production of intracellular bacterial communities and promote trafficking through the endolysosomal pathway were revealed through the use of pharmacological inhibition of macropinocytosis. This work demonstrates the importance of an intracellular niche for NTHI and provides new approaches for intervention for acute, chronic, and recurring episodes of otitis media.